3z-10=3-5(z+11)

Simple and best practice solution for 3z-10=3-5(z+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3z-10=3-5(z+11) equation:


Simplifying
3z + -10 = 3 + -5(z + 11)

Reorder the terms:
-10 + 3z = 3 + -5(z + 11)

Reorder the terms:
-10 + 3z = 3 + -5(11 + z)
-10 + 3z = 3 + (11 * -5 + z * -5)
-10 + 3z = 3 + (-55 + -5z)

Combine like terms: 3 + -55 = -52
-10 + 3z = -52 + -5z

Solving
-10 + 3z = -52 + -5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '5z' to each side of the equation.
-10 + 3z + 5z = -52 + -5z + 5z

Combine like terms: 3z + 5z = 8z
-10 + 8z = -52 + -5z + 5z

Combine like terms: -5z + 5z = 0
-10 + 8z = -52 + 0
-10 + 8z = -52

Add '10' to each side of the equation.
-10 + 10 + 8z = -52 + 10

Combine like terms: -10 + 10 = 0
0 + 8z = -52 + 10
8z = -52 + 10

Combine like terms: -52 + 10 = -42
8z = -42

Divide each side by '8'.
z = -5.25

Simplifying
z = -5.25

See similar equations:

| -9=-6(x-5) | | (x+5)+(3x-2)=280 | | -9=-6(x+5) | | 126+y=180 | | 4x-9+2x=-6x+5-3 | | 3*4+14-5-[-2]*7=-23 | | x+54=y | | -3k-1=12 | | x=3y(y+w)-1 | | k=5/8m | | 4x-9+2x=-6x+5 | | 6(3x+2)+5(7x-6)-12x=6(x-3)+5(6x-1) | | X^2-8x=100 | | 7xy+2y^2=1 | | 20y^4+35y^3+15y^2= | | 78-u=271 | | -1(t^2-3t-10)=0 | | -1=5-2x/3 | | x-23=x+77 | | -98/-18 | | (-8-90)/2(-8)-2 | | (-8-90)/2x(-8)-2 | | 4m^2-36mn+81n^2= | | x+4.9=6.89 | | 2.6x-52=1.3x | | 2.6x-52=1.3 | | 5x-27=x+30 | | 8ab^2-12a^2b= | | 2(y+x)=-(-3x+10) | | 29-35=-5 | | 8x-20=2x+40 | | 4x-7=-x-9 |

Equations solver categories